Management of neonates with respiratory distress syndrome in resource-limited settings - Radhika Singh; Leann P. Munian; Nqobile A. Memela (South African Family Practice, 2024)
In South Africa, prematurity stands as one of the foremost causes of neonatal mortality. A significant proportion of these deaths occur because of respiratory distress syndrome of prematurity. The implementation of non-invasive respiratory support, such as continuous positive airway pressure (CPAP), has demonstrated both safety and efficacy in reducing mortality rates and decreasing the need for mechanical ventilation. Given the absence of blood gas analysers and limited radiological services in many district hospitals, the severity of respiratory distress is often assessed through observation of the infant’s work of breathing and the utilisation of bedside scoring systems. Based on the work of breathing, non-invasive therapy can be commenced timeously. While evidence supporting the use of high-flow nasal cannula as a primary treatment for respiratory distress syndrome remains limited, it may be considered as an alternative, provided that CPAP machines are available. The purpose of this article is to advocate the use of non-invasive therapy in low resource-limited settings and describe the indications, contraindications, complications, and application of CPAP therapy. This would benefit healthcare workers, especially in low-care settings and district hospitals.